2013
DOI: 10.1128/jcm.02863-12
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time PCR Quantification of Methanobrevibacter oralis in Periodontitis

Abstract: bA real-time PCR assay developed to quantify Methanobrevibacter oralis indicated that its inoculum significantly correlated with periodontitis severity (P ‫؍‬ 0.003), despite a nonsignificant difference in prevalence between controls (3/10) and patients (12/22) (P ‫؍‬ 0.2, Fisher test). The M. oralis load can be used as a biomarker for periodontitis. Periodontitis is an anaerobic infection possibly leading to loss of teeth (1-3). It likely results from infection with microbial complexes comprising methanogens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 17 publications
5
37
0
Order By: Relevance
“…The mean amount of methanogens per sample was found to be 10 6 target molecule numbers (standard error: 4 Â 10 5 ). Both, prevalence and quantity were in rough accordance to previous studies [1,2,17]. There was no discernable relationship of methanogenic prevalence or abundance with gender.…”
supporting
confidence: 92%
“…The mean amount of methanogens per sample was found to be 10 6 target molecule numbers (standard error: 4 Â 10 5 ). Both, prevalence and quantity were in rough accordance to previous studies [1,2,17]. There was no discernable relationship of methanogenic prevalence or abundance with gender.…”
supporting
confidence: 92%
“…Another finding that deserves attention in the present review concerns the Archaea domain, which also fell into the moderate evidence category. Among the 41 studies included in this review, only 5 searched for Archaea, and 4 of them showed an association between this domain and periodontitis (Lepp et al, 2004;Li et al, 2009;Matarazzo et al, 2011;Bringuier et al, 2013). Although the fifth study (Vianna et al, 2008) did not find statistically significant higher prevalence or counts of metanogenic Archaea in subjects with periodontitis in comparison with periodontally healthy subjects, this taxa was not detected in any of the healthy subjects evaluated.…”
Section: Discussionmentioning
confidence: 92%
“…We recently demonstrated a significant correlation between the M. oralis charge and the severity of periodontitis (3). Furthermore, M. oralis DNA was detected in the human gut, and we previously reported the first isolation of M. oralis (strain JMR01) from the human gut (4).…”
Section: Genome Announcementmentioning
confidence: 99%